Digital interprofessional communication with families in a cardiac surgery unit: insights from the pandemic - Pozzoli, Alberto; Zurfluh, Chantal; Schulz, Peter; Bianchi, Monica; Giuffrida, Silvia; Crivelli, Diego; Torre, Tiziano; Ferrari, Enrico; Demertzis, Stefanos (Frontiers in Cardiovascular Medicine, 2023)
Background The COVID-19 pandemic entailed cutting off the usual access to hospitals, denying patients daily visits from their relatives and friends. The standard communication between medical staff and relatives also suffered, with a perceived negative impact on overall care. We developed an electronic communication solution to re-establish a proactive daily communication with patients’ families. Methods The communication software allowed families to receive daily interprofessional (medical, nursing, and physiotherapy) updates by text message, on patients’ postoperative clinical state. Appreciation and performance of this communication was evaluated through a prospective randomised study. Two groups were compared (group D, 32 patients “Digital” receiving daily SMS, and group S, 16 patients “Standard” without SMS), assessing satisfaction through dedicated surveys under COVID-19 restrictions. Moreover, private outgoing vs. incoming communication flow between patients and their relatives (phone calls and text messages, for both groups) were analysed at different timeframes of the postoperative hospital stay. Results Mean age of the population was 66 ± 7 years for both groups. The digital communication service was successfully adopted in group D in all cases, sending overall 155 communications (4.84 per patient). Calls received from relatives were 13 in group D vs. 22 in group S (0.4 vs. 1.4 calls per patient, p = 0.002). Patients’ outgoing vs. incoming traffic flow was equal in the two groups for every timeframe (first two postoperative days vs. the rest), independently from digital communication. Comparing satisfaction of communication (from 1 to 7), level of information and understandability resulted in 6.7 in group D vs. 5.6 in group S (p = 0.004). Appreciation of digital communication was highest during the first three postoperative days. Conclusion The restrictions caused by the COVID-19 pandemic generated simple and effective ideas on digital solutions for interprofessional communication. Offering this digital service, which complements rather than replace the classic communication, eased the need of the families to be informed and significantly enhanced the overall satisfaction regarding the healthcare service. Summary The COVID-19 pandemic has interrupted access to hospital patients and cut off physical contact, denying patients, their families, and medical staff the necessary constant communication about the progress of their stay. It has become necessary, therefore, to compensate for the lack of “physical” face-to-face interaction by introducing innovative digital communication solutions. Our interprofessional project aims to assess the overall satisfaction and acceptance of digital communication service between the hospital and the families, updating on postoperative clinical condition of patients. Specifically, the introduction of a digital communication module attached to the electronic patient record allows relatives to be informed on a daily basis. The development of this module/software enabled families to receive daily, interprofessional and proactive digital updates, on their relative ones’ postoperative stay.